Etoposide/platinum plus anlotinib for patients with transformed small-cell lung cancer from EGFR-mutant lung adenocarcinoma after EGFR-TKI resistance: a retrospective and observational study - Ding, Jianghua; Leng, Zhaohui; Gu, Hong; Jing, Xiang; Song, Yun (Frontiers in Oncology, 2023)
Objective: The histological conversion of lung adenocarcinoma (LUAD) into small-cell lung cancer (SCLC) is an important resistance mechanism for epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI)-resistant LUAD. Anlotinib has been recommended as the third-line treatment for SCLC patients. The efficacy of etoposide/platinum (EP) as the main treatment is very limited for patients with transformed SCLC. However, little is known about EP plus anlotinib for transformed SCLC. The present study retrospectively explored the clinical response to EP combined with anlotinib in patients with transformed SCLC from LUAD after EGFR-TKI failure. Methods: A total of 10 patients who underwent SCLC transformation from EGFR-TKI-resistant LUAD were retrospectively reviewed from September 1, 2019, to December 31, 2022, in three regional hospitals. All of the patients were treated with the combination regimen of EP and anlotinib for four to six cycles, followed by anlotinib maintenance therapy. The clinical efficacy indices including objective response rate (ORR), disease control rate (DCR), median progression-free survival (mPFS), median overall survival (mOS), and toxicities were evaluated. Results: The median time from EGFR-TKI treatment to SCLC conversion was 20.1±2.76 months (17–24 months). Genetic examination after transformation showed that 90% of the patients retained their original EGFR gene mutations. Additional driver genes included BRAF mutation (10%), PIK3CA mutation (20%), RB1 loss (50%), and TP53 mutation (60%). The ORR and DCR were 80% and 100%, respectively. The mPFS was 9.0 months (95% CI, 7.9–10.1 months), and the mOS was 14.0 months (95% CI, 12.0–15.9 months). Less than 10% of grade 3 toxicities were observed, and no grade 4 toxicity and death events were reported. Conclusion: The EP plus anlotinib regimen appears to be a promising and safe strategy in transformed SCLC patients after EGFR-TKI resistance, which warrants further investigation.